Event Study of Effect of Merger Announcement on Stock Price in Nepal - Chhetri, Shanti Devi; Baral, Ravindra Prasad (Journal of Business and Management, 2018)
Events like merger and acquisition affect the value of merging firms and also generate a positive or negative wealth effect for shareholders of firms involved. The purpose of this study is to investigate whether a merger announcement has generated wealth effects for the shareholders of bidding and target firms as well as it has aimed to assess the impact on overall banking sector. Two models; mean adjusted model and market risk adjusted model has been used in the study employing the ‘event study’ methodology to examine whether there is presence of abnormal return associated with merger announcement. In this method, 50 days premerger and 30 days post merger period is assumed as estimation period and (-15 and +15) days are taken as the window period. Fifteen financial institutions which entered into merger between years 2010 to 2012 are selected as sample. The findings of this study demonstrated that surrounding the announcement of merger proposals, the premerger abnormal return of individual firms is not significant to zero i.e. return is not affected by the merger announcement. Similarly, the abnormal return of bidding and target firms is not significant which indicates there is no impact of merger announcements on shareholder wealth in Nepalese capital market. Finally, the abnormal return during the premerger and post merger period of individual firms as well as the overall banking sector shows the same result, there is no significant difference on return before and after the merger announcement.